Interpreting collaborative reasoning and instructional strategies in argumentative writing - Masrul, Masrul; Yuliani, Sri (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
This experimental study combined collaborative reasoning and instructional strategies as an alternative in argumentative writing. This is important to determine the extent to which the combination of these approaches can enhance students' writing skills. Collaborative reasoning is an approach in learning where students collaborate to formulate thoughts or solutions to a problem. Meanwhile, instructional strategies refer to the approaches and methods used by teachers to guide students in understanding and developing argumentative writing skills. The study took place at SMAN 1 Bangkinang Kota, Riau province, Indonesia. There were 100 students from second grade who participated. The results of the study showed that the combination of the socially-oriented approach in the forms of collaborative reasoning and instructional strategies in argumentative writing by the treatment group was more effective than the control group. Innovative teaching strategies are beneficial for both students and teachers. The combination has helped students develop better writing ability.